Translating Religious Texts Through Rechecking Semantic-Communicative Analysis: Integrating SDGs Into Translation Studies - Mujazin; Anam Sutopo; Nuria Siswi Enggarani; Alaa Alkhateeb (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to develop a religious text translation model based on rechecking semantic-communicative analysis to improve translation quality. The model supports semantic accuracy, cultural sensitivity, and moderation in line with the Sustainable Development Goals (SDGs). Theoretical framework: This research integrates semantic and communicative translation theory, cognitive-communicative approaches, functional translation principles, and hermeneutic interpretation. These frameworks collectively support a holistic and ethically grounded approach to religious translation. Literature review: Previous studies on religious translation focus mainly on isolated linguistic or cultural strategies, with limited integration of systematic rechecking and SDGs perspectives. This study addresses the gap by proposing an integrated semantic-communicative and contextual model. Methods: This study employs a qualitative approach using data from Islam: A Short History and focus group discussions with Qur’an translation teachers. Semantic-communicative analysis, rechecking procedures, and hermeneutic interpretation are applied to ensure accuracy and contextual relevance. Results: The findings indicate that religious text translation faces challenges related to semantic non-equivalence and cultural context. Integrating semantic-communicative analysis improves readability and meaning accuracy. Rechecking procedures effectively reduces the distortion of key religious terms. Implications: The study highlights the need for translator training that integrates linguistic and religious knowledge. It also supports the use of contextualized glossaries and cautious machine translation with rechecking mechanisms in line with the SDGs. Novelty: The novelty of this research lies in its holistic and replicable translation model integrating semantic-communicative analysis, expert-based rechecking, and hermeneutic interpretation. This approach advances translation studies by linking linguistic accuracy with ethical and sustainable knowledge transmission.